Advancing Systems Epidemiology in Cancer - Exploring Trajectories of Gene Expression - Eiliv Lund (Scandinavian University Press (Universitetsforlaget), 2020)
This book introduces systems epidemiology, which is a new scientific discipline borne by novel technologies. These have opened up the potential for studies of temporal changes in the carcinogenic process and the response of the immune system, all measured as functional genomics: gene expression, microRNA and methylation. Systems epidemiology is an integrated approach based on epidemiological methods with biobanks designed for studies of the trajectories or curves of functional genomics moving from before diagnosis, at diagnosis and postdiagnostic. It demands new epidemiological designs, the globolomic one, new statistical methods for description and analyses of time changes and incorporating basic knowledge from reductionist experiments and clinical outcomes including molecular biomarkers of cancer tissue and normal tissues.